Analizar el control y gestión de inventario en la Hacienda Mercedes Belén del Cantón Baba periodo 2022. - Rosero Luna, Marilin Esther (2023)
This case study is focused on the analysis and inventory management of the Mercedes Belén Hacienda in the Baba canton. with Single Taxpayer Registry number 0701889321-001 which has as its main economic activity the cultivation of bananas and plantains. The objective of inventory control and management is the registration of inputs and outputs of materials in chronological time, in order to calculate the complete and correct costs. The inventory control and management system allows stock levels to be maintained, avoiding excesses or shortages of materials. It is examined in the line of research Financial, administrative, tax, audit, control management, which is related to the subject, where it is verified if the company's inventory accounting processes are sufficient to make adequate decisions with the necessary information from tools where it allows to observe the control and current management of the inventory that is carried in the hacienda mercedes belen period 2022. Through the subline of investigation of the present work that is Audit and Control, it allows to establish if the activities that are executed in the accounting area and warehouse. It can be concluded that the state of inventory control and management at Hacienda Mercedes Belén is deficient and lacks control, which was very evident given that it was reflected in the losses of materials used for production, taking into consideration that this subtracts liquidity to the organization, which in the long term can affect the consistency of the company.